Antifibrotic Effect of Boric Acid in Rats with Epidural Fibrosis - (:unkn) unknown (ELSEVIER SCIENCE INC, 2019)
BACKGROUND: Epidural fibrosis is a major problem after spine surgery, with some patients having recurrent symptoms secondary to excessive formation of scar tissue resulting in neurologic compression. We used a rat laminectomy model to determine if topical application of boric acid could be helpful in the prevention of epidural fibrosis. METHODS: Rats were randomly assigned to 2 control and 2 experimental groups (n = 8 for each group). The negative control group received no surgery, and the positive control group underwent laminectomy only. Experimental groups were classified according to the study agents applied onto the dura mater after laminectomy at the L3 level: 2.5% boric acid solution and 5% boric acid solution. The extent of epidural fibrosis was assessed 4 weeks later macroscopically and histopathologically. RESULTS: Boric acid reduced epidural fibrosis in rats after laminectomy. The effect of 5% boric acid solution was more pronounced (P < 0.05) compared with the 2.5% solution. CONCLUSIONS: The antifibrotic effect of boric acid solution for the prevention of epidural fibrosis suggests that boric acid should be further evaluated in future studies for the prevention of epidural fibrosis.
Keywords: Boric acid; Epidural fibrosis; Laminectomy; DIETARY BORON; PROSTATE; MIGRATION